The centenary of Luiz Gonzaga: the construction of the sertaneja identity (Revista Internacional de Folkcomunicação, 2018)
ABSTRACT This article deals with the analysis of the special TV show about the centenary of Luiz Gonzaga, through the study of cultural identities for the preservation of intangible cultural heritage. We analyze the importance of the study of cultural identities in contemporary times, in the formation and preparation of the professional journalism, aiming at a more efficient mediation process and a more humanized journalism. The corpus analyzed was the reporting on the "Centenary of Luiz Gonzaga", elaborated and introduced by the program Globo Rural, on 12.12.2012. KEY-WORDS Globo Rural; Luiz Gonzaga; Journalism; Intangible Heritage; Cultural Identity,